Physical Properties of Four Varieties of Sorghum (Sorghum Bicolor L. Moench) Grain at Different Moisture Contents - Kawuyo, U. A.; Aviara, N. A.; Mari, H. H.; Ahmed, B. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This study was undertaken to determine the physical properties of four varieties of sorghum grain and investigate their variation with moisture content. The properties studied include: axial dimensions, arithmetic mean and geometric mean diameters, one thousand grain weight, particle density, bulk density, porosity and angle of repose. Each property was investigated at four moisture levels in the range of 3.5-18.25% d.b (brown variety), 3.04-25.49% d.b (red variety), 3.5-20% d.b (reddish brown variety) and 3.4-25.49% d.b (white variety). The major, intermediate and minor dimensions all increased with increase in moisture content from 4.25-5.04mm, 4.10-4.76mm and 2.80-2.99mm for brown, 3.78-4.32mm, 2.96-3.43mm and 1.95-2.85mm for red, 4.25-5.21mm, 4.11-4.99mm, 3.61-3.77mm for reddish brown, 4.0-5.38mm, 3.20-4.99mm and 3.00-3.48mm for white variety. The arithmetic mean diameter had higher values for the four varieties than the geometric mean diameter. One thousand grain weight, bulk density, true density, porosity, and angle of repose of all the varieties of sorghum studied, increased linearly with increase in moisture content. Regression models with high coefficients of determination were used to express the relationship existing between the physical properties of the grains with moisture content.